2017
DOI: 10.5194/amt-10-4055-2017
|View full text |Cite
|
Sign up to set email alerts
|

Precipitable water characteristics during the 2013 Colorado flood using ground-based GPS measurements

Abstract: Abstract. During 9-16 September 2013, the Front Range region of Colorado experienced heavy rainfall that resulted in severe flooding. Precipitation totals for the event exceeded 450 mm, damages to public and private properties were estimated to be over USD 2 billion, and nine lives were lost. This study analyzes the characteristics of precipitable water (PW) surrounding the event using 10 years of high-resolution GPS PW data in Boulder, Colorado, which was located within the region of maximum rainfall. PW in B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Reported in [16] is a severe flood, caused by intense rainfall, in Colorado, USA, from 9 to 16 September 2013. Analysis of IWV for the 10-year period showed that in 2013: (1) the seasonal IWV maximum extended into early September, and (2) the September monthly mean IWV exceeded the 99th percentile of climatology with a value 25% higher than the 40-year climatology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported in [16] is a severe flood, caused by intense rainfall, in Colorado, USA, from 9 to 16 September 2013. Analysis of IWV for the 10-year period showed that in 2013: (1) the seasonal IWV maximum extended into early September, and (2) the September monthly mean IWV exceeded the 99th percentile of climatology with a value 25% higher than the 40-year climatology.…”
Section: Introductionmentioning
confidence: 99%
“…The IWV frequency distribution in September was typically normal, while in 2013, a bimodal distribution was found with above-average IWV from 1 to 15 September, and much drier conditions from 16 to 30 September. The positive IWV anomaly during the flood was found to be a result of large-scale moisture transport from the Tropical Eastern Pacific and the Gulf of Mexico [16]. The potential of high-frequency IWV (5 and 15 min) in combination with weather radar reflectivity was exploited by [17] for a derecho event in Poland on 11 August 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the frequency distributions of PWV and temperature are also analyzed in August 2014 to verify the extreme climatic anomaly [12,33]. Figure 5 gives the statistical frequency distributions of PWV and temperature for Augusts from 2010 to 2017 using the data from the ECMWF ERA-Interim data.…”
Section: Abnormality Of Climatic Factors In August 2014mentioning
confidence: 99%
“…The Global Navigation Satellite Systems (GNSS) technique was proved to be able to detect sudden changes in precipitable water vapor (PWV) [6][7][8][9] and has been widely used in the monitoring of atmospheric storms and depressions [10] as well as the forecasting of heavy precipitation [11]. The authors of [12] pointed out that the PWV characteristics are an important factor because they could affect future climate change trends. Additionally, PWV variations are highly correlated with precipitation, and precipitation begins normally after the PWV reaches its peak and PWV returns to its climatological value after the end of the precipitation [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation